2023
DOI: 10.1088/1402-4896/acc987
|View full text |Cite
|
Sign up to set email alerts
|

Novel propagation phenomena: behaviors of local trend imitation on multiple limited contact networks

Abstract: The local trend imitation(LTI) feature behavior has been deeply studied on specific complex networks, but still needs to be explored in more scenarios. In fact, the multiple networks with individual limited contact feature is more in line with the real scenario On the multiple limited networks,a novel model is proposed to investigate the effects of individual contact capacity heterogeneity. Then,information propagation mechanism is then measured and examined using a developed partition theory. The experimental r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…In fact, when disease outbreak occurs, disease-related information also diffuses among the population, and we learn about the risk of the disease and some preventive measures based on this information as a way to reduce our risk of being infected, which in turn has an important impact on the transmission of the disease [20][21][22][23][24][25]. Funk et al [22] analyzed the law of disease transmission based on the SIR model, and found that the diffusion of information can reduce the scale of the transmission of the disease; Granell et al [23] established UAU-SIS twolayer network model to study the coupled information and disease spreading law, and found that information can effectively inhibit disease transmission at the meta-critical point.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, when disease outbreak occurs, disease-related information also diffuses among the population, and we learn about the risk of the disease and some preventive measures based on this information as a way to reduce our risk of being infected, which in turn has an important impact on the transmission of the disease [20][21][22][23][24][25]. Funk et al [22] analyzed the law of disease transmission based on the SIR model, and found that the diffusion of information can reduce the scale of the transmission of the disease; Granell et al [23] established UAU-SIS twolayer network model to study the coupled information and disease spreading law, and found that information can effectively inhibit disease transmission at the meta-critical point.…”
Section: Introductionmentioning
confidence: 99%